Role of Mitochondria-Related Genes in NSCLC: Prognostic Implications and Immune Microenvironment Influence - Zhenye Pu; Bin Liu; Jin Fang; Yang Hu; Tao Xue; Hongyan Li (International Journal of Clinical Practice)
Conclusion: Mitochondria-related genes significantly impact the prognosis of NSCLC and may influence the immune microenvironment and responses to immunotherapy. These findings enhance our understanding of NSCLC and suggest potential targets for future therapeutic interventions.